Studying the Reasons behind the Occurrence of Cracks in the Bucket Elevator in the Lebda Cement Factory (المجلة الدولية للبحوث العلمية, 2024)
Bucket elevators always face problems during the accumulation of loads. When buckets are damaged, the bucket elevator breaks down. Replacing or repairing damaged buckets increases overall maintenance costs; it takes technicians at least several days, depending on how severe the damage is, which will result in decreased productivity and increased downtime. The main goal of this paper is to find out the reason for the cracks that occur at the edges of the bucket conveying cement in the Al- Lebda Cement Factory. According to the manufacturer's catalogue, the material of the bucket is made of EU EN S235JR steel.To study this problem, we conducted a series of tests on samples of the bucket's metal, including chemical composition analysis, tensile strength testing, hardness testing, and microscopic examination. We then compared the results of these tests to the standard specifications for the S235JR steel grade. The results of bucket samples showed the carbon content was C 0.1107 Wt. %, yield strength was 350 N/mm2, ultimate tensile strength was 445 N/mm2 and hardness test was 77HRB, and the metallurgical analysis indicated an irregular distribution of the grain boundaries with, the accumulation of cementite in several areas. It should be noted that the temperature of the cement was not taken into consideration in this study.